2014
DOI: 10.1088/2041-8205/788/2/l21
|View full text |Cite
|
Sign up to set email alerts
|

THE PECULIAR EXTINCTION LAW OF SN 2014J MEASURED WITH THE HUBBLE SPACE TELESCOPE

Abstract: The wavelength-dependence of the extinction of Type Ia SN 2014J in the nearby galaxy M82 has been measured using UV to near-IR photometry obtained with the Hubble Space Telescope, the Nordic Optical Telescope, and the Mount Abu Infrared Telescope. This is the first time that the reddening of a SN Ia is characterized over the full wavelength range of 0.2-2 µm. A total-toselective extinction, R V ≥ 3.1, is ruled out with high significance. The best fit at maximum using a Galactic type extinction law yields R V =… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
143
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(166 citation statements)
references
References 36 publications
23
143
0
Order By: Relevance
“…The extinction feature is also similar to what is seen in rare cases of reddened supernovae and active galactic nuclei Leighly et al 2014;Amanullah et al 2014). These systems have been successfully modelled with the prescription for multiple scattering of light discussed in Wang (2005) and Goobar (2008).…”
Section: Extinction With Multiple Scatteringsupporting
confidence: 78%
See 1 more Smart Citation
“…The extinction feature is also similar to what is seen in rare cases of reddened supernovae and active galactic nuclei Leighly et al 2014;Amanullah et al 2014). These systems have been successfully modelled with the prescription for multiple scattering of light discussed in Wang (2005) and Goobar (2008).…”
Section: Extinction With Multiple Scatteringsupporting
confidence: 78%
“…Ca i, Ca ii, CH + ). The closest local analogue to the region causing the dust extinction is probably the sightline to SN 2014J in in the starburst galaxy M 82: along this sightline similar extinction is seen (Amanullah et al 2014). Furthermore, similar absorption line properties are also seen, e.g.…”
Section: Discussionmentioning
confidence: 67%
“…Extinction curves steeper than the MW with R V = 2.4-2.5 and a bump at 2175 Å are detected in the central M31 bulge (Dong et al 2014). Amanullah et al (2014) found a steep extinction curve with R V = 1.4 for a Type Ia supernova SN 2014JA in the starburst galaxy M82. A sample of ∼2000 UV-deficient narrow line Seyfert galaxies also shows a steeper extinction law (Zhou et al 2006).…”
Section: Comparison Of Steep Extinction Curvesmentioning
confidence: 86%
“…Low R V values can also be seen along the lines of sight to individual SNe Ia (e.g. Amanullah et al 2014Amanullah et al , 2015.…”
Section: Introductionmentioning
confidence: 99%